Relevance of Neuroinflammation and Encephalitis in Autism - Kern, Janet K.; Geier, David A.; Sykes, Lisa K.; Geier, Mark R. (Frontiers in Cellular Neuroscience, 2016)
In recent years, many studies indicate that children with an autism spectrum disorder (ASD) diagnosis have brain pathology suggestive of ongoing neuroinflammation or encephalitis in different regions of their brains. Evidence of neuroinflammation or encephalitis in ASD includes: microglial and astrocytic activation, a unique and elevated proinflammatory profile of cytokines, and aberrant expression of nuclear factor kappa-light-chain-enhancer of activated B cells. A conservative estimate based on the research suggests that at least 69% of individuals with an ASD diagnosis have microglial activation or neuroinflammation. Encephalitis, which is defined as inflammation of the brain, is medical diagnosis code G04.90 in the International Classification of Disease, 10th revision; however, children with an ASD diagnosis are not generally assessed for a possible medical diagnosis of encephalitis. This is unfortunate because if a child with ASD has neuroinflammation, then treating the underlying brain inflammation could lead to improved outcomes. The purpose of this review of the literature is to examine the evidence of neuroinflammation/encephalitis in those with an ASD diagnosis and to address how a medical diagnosis of encephalitis, when appropriate, could benefit these children by driving more immediate and targeted treatments.